Audit Effort, Audit Fees, and the Provision of Nonaudit Services to Audit Clients. - Davis, Larry R.; Ricchiute, David N. (The Accounting Review, 1993)
Examines whether the provision of audit clients with nonaudit services result in knowledge spillovers and audit production efficiencies that could produce economic rents for the auditor. Demonstration of the comparability of the research sample with prior studies; Data set compiled from the participating firm's internal billing records.